2008
DOI: 10.1111/j.1863-2378.2008.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to an Anti‐rabies Vaccine in a Dog Population under Field Conditions in Bolivia

Abstract: Rabies remains an important public health issue in Bolivia, South America. Public concern and fears are most focussed on dogs as the source of rabies. The objective of the present study was to assess immunity of an inactivated suckling mouse brain vaccine against canine rabies used for the official vaccination campaigns under field conditions in an endemic area of rabies in Bolivia. A total of 236 vaccinated and 44 unvaccinated dogs in Santa Cruz de la Sierra, selected using stratified random sampling, were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
4
8
0
3
Order By: Relevance
“…There were animals in other groups with past vaccination history who did not have adequate protection. Similar patterns of data had been observed by research groups in other countries as well [ 33 35 ]. However, Barth et al, indicates by analyzing many experimental results that dogs have a very high probability of survival after a later rabies infection, even if serum does not contain detectable anti-rabies antibodies irrespective of the period of time elapsed since the vaccination [ 18 ].…”
Section: Discussionsupporting
confidence: 88%
“…There were animals in other groups with past vaccination history who did not have adequate protection. Similar patterns of data had been observed by research groups in other countries as well [ 33 35 ]. However, Barth et al, indicates by analyzing many experimental results that dogs have a very high probability of survival after a later rabies infection, even if serum does not contain detectable anti-rabies antibodies irrespective of the period of time elapsed since the vaccination [ 18 ].…”
Section: Discussionsupporting
confidence: 88%
“…This could indicate that the dogs in Emalahleni do not seroconvert as efficiently as dogs that have better access to veterinary care. The geometric mean titre 30-60 days post-vaccination within this study (1.44 IU/ ) compares favourably with other studies 29,37,39 . However, as the number of vaccinations a dog had received before the study could not be verified, further interpretation of this result was not attempted.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, 43 % of dogs whose owners reported previous vaccination had antibody titres of 0.5 IU/ or above. This response is lower than the percentage in other communities: a study in Spain found it to be 58 % 12 ; in urban Bolivia it was also found to be 58 % 39 ; in rural and peri-urban Kenya it was 48 % 23 and in urban Botswana 52 % 36 . Considering that the owner's responses regarding the vaccination status of their dogs could not be verified, it becomes difficult to evaluate the low proportion of dogs with adequate neutralising antibody titres in Emalahleni, but it may, amongst others, be attributable to: low vaccination coverage by AHTs in the preceding rabies campaign, a rapid drop in antibody titre after being vaccinated in the preceding campaign and/or incorrect handling and administration of vaccines during campaigns.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The disease still remains a very important public health problem in Nigeria posing serious fear to the populace (Suzuki et al, 2008), and about 10,000 annual human cases were reported in Nigeria (Nawathe, 1980). The disease has remained an endemic problem in Nigeria since it was first reported in 1912 (Umoh and Belino, 1978;Nawathe, 1980).…”
Section: Introductionmentioning
confidence: 99%